On possibility of applying parts produced by additive technology in high pressure gate valves; Междисциплинарные проблемы аддитивных технологий - Kuznetsov V. P.; Skorobogatov A. S.; Fefelov A. S.; Kolmakov S. V.; Anikeev A. V. (2017, 2017)
Заглавие с титульного экрана